ChemInform Abstract: Review on Fungal Enzyme Inhibitors — Potential Drug Targets to Manage Human Fungal Infections. Issue 26 (June 2016) - Ramakrishnan, Jayapradha; Rathore, Sudarshan Singh; Raman, Thiagarajan
Abstract: Review: 148 refs.